2017
DOI: 10.21873/anticanres.11736
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy for Coping with Cancer Enhances the Effect of Reiki Treatments During the Pre-Surgery Phase of Breast Cancer Patients

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Another important point in this context is that higher self-efficacy goes along with a higher effect of alternative treatments as Reiki which depend on a high placebo effect [ 17 ]. In fact, this would also explain the affinity of high self-efficacious patients to homeopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Another important point in this context is that higher self-efficacy goes along with a higher effect of alternative treatments as Reiki which depend on a high placebo effect [ 17 ]. In fact, this would also explain the affinity of high self-efficacious patients to homeopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study showed that there was a relationship between self-efficacy and the quality of life of cancer patients who underwent chemotherapy before self-efficacy training with p 0,000 having moderate relationship strength (r=0,491), after training with p 0,000 having strong relationship strength (r=0,600), after 4 weeks training with p 0,000 has the strength of strong relationship (r=0,624). Several studies have suggested that there was a strong relationship between self-efficacy and quality of life in cancer patients and the therapy they undergo (Chirico, 2017;Omran & Mcmillan,2018). The results of the study also showed that the mean difference in self-efficacy scores before the intervention and after the intervention was (9,98±0,69) and there was an effect of self-efficacy training on the self-efficacy of cancer patients undergoing chemotherapy with a p value of 0,000 < 0,05.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy is an important component in cancer patients. Based on that the condition can be a trigger factor or a factor that reduces the occurrence of cancer (Lev, 1999;Cunningham, 1991;Chirico et al, 2017). Patients who are diagnosed with cancer will be faced with the actions that they will receive and this will have an effect on their self-efficacy (Mystakidou et al, 2012;Akin, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with high self-efficacy as a result of physical exercises or treatments such as Reiki had a better psychological adaptation were able to manage their anxiety better and their anxiety decreased. In recent studies, self-efficacy has been defined as an important predictor of an active adaptation style and emotional well-being in cancer patients (Chirico, D'Aiuto, et al, 2017;Geng et al, 2018;Koehler et al, 2009). Another study investigating the relationship between the problem-focused coping and self-efficacy in patients with stroke found a strong relationship (Tielemans et al, 2015).…”
Section: Ta B L Ementioning
confidence: 99%